Assessment of Cognitive Abilities and Impact of Parental Intellectual Level in ASD Children - Chaima, Smili; Amina, Djouini; Fella, Chebbah; Islam, Hamida Youcef; Amira, Bakeche; Rania, Soual; Abdelmadjid, Bairi (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Autism, now called Autism Spectrum Disorder (ASD), includes children with autism, but also those with Asperger's Syndrome and those with Pervasive Developmental Disorder Not Otherwise Specified. In order to learn more about the subject, we were interested in a population of 30 children with ASD aged 10±5 years from the region of Annaba, Algeria, accommodated as half-boarders at the Centre Médico-Pédagogique pour Enfants Handicapés Mentaux. These children are divided by the psychologist of the center into 4 groups according to their degree of impairment (from mild to severe). To classify them, several criteria had to be considered such as the child's comprehension, independence and responsiveness. The study consists of assessing their cognitive abilities on a daily basis and over a period of 20 days. On the other hand, to collect testimonies from parents and the role they can play to help with these neurodevelopmental anomalies. The results reveal impairments in the ability to establish social interactions and to communicate, as well as cognitive abnormalities, in particular reluctance to change and tendencies to repeat behaviour or speech. Some of them, often isolated in their inner world, show particular sensory reactions (auditory, visual, skin...). We also note that the parents' level of education has a strong impact on their position regarding this disorder. That is, the higher it is, the more likely they are to accept their different children. These advances suggest that, for the coming years, ASD in Algeria should occupy a special place in public health policy. It is therefore time to sound the alarm and invest in multidisciplinary research to understand more about its mechanisms but above all to improve its management.